2019
DOI: 10.12691/ajnr-7-4-25
|View full text |Cite
|
Sign up to set email alerts
|

The Oral Health Knowledge and Self-care Practices of Pregnant Women in Saudi Arabia

Abstract: Background. Pregnancy is a unique time in a woman's life and is characterized by complex physiological changes. These changes can adversely affect oral health. Oral health is a state of being free from chronic mouth and facial pain, oral and throat cancer, oral sores, periodontal (gum) disease, tooth decay and tooth loss, and other diseases, and disorders that affect the oral cavity. Risk factors for oral diseases include unhealthy diet, tobacco use, harmful alcohol use, and poor oral hygiene (WHO). Multiple s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…This amount showed that pregnant women who did not have a dental examination was higher than those who had an examination. This result was almost the same as with the research conducted by Moawed et al 6 which stated that as many as 65% of pregnant women did not go to the dentist.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This amount showed that pregnant women who did not have a dental examination was higher than those who had an examination. This result was almost the same as with the research conducted by Moawed et al 6 which stated that as many as 65% of pregnant women did not go to the dentist.…”
Section: Discussionsupporting
confidence: 89%
“…7 The results of the present study indicated that recommendation of oral health programs in prenatal services is essential to the delivery of dental care and decreasing the potential oral problems among pregnant women, as well as conducting a careful initial screening of oral risks, and assisting women in obtaining regular dental care. 6 As many as 83.72% of 129 pregnant women go to the dentist purely because of their own's will, while only very few of them get direction from their family (Table 3). These results were slightly different from the research conducted by Karasu et al 8 which stated that during their pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In Saudi Arabia, the delivery of health services is supervised and nanced by the Ministry of Health [MOH] and oral healthcare is integrated into prenatal care [22]. Nonetheless, more than half of the pregnant women in Saudi Arabia completely avoid dental care during pregnancy and most access dental care only when they have toothache or bleeding gums [11,[13][14][15][16]23]. The most reported barriers to the utilization of dental care during pregnancy were low awareness of the importance of oral healthcare, negative perceptions regarding the safety of dental treatment, and lack of perceived need for dental care [11,14,16,[23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, 70-90% of pregnant women have at least one dental problem [13][14]. Periodontal disease was the most (30-60%) prevalent dental problem, followed by dental caries and toothache [30-40%] [13,[15][16]. Periodontal disease during pregnancy is associated with adverse birth outcomes, such as preterm birth and low birth weight [17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, the delivery of health services is supervised and nanced by the Ministry of Health, and oral healthcare is integrated into prenatal care [22]. Nonetheless, more than half of the pregnant women in Saudi Arabia completely avoid dental care during pregnancy, and most access dental care only when they have toothache or bleeding gums [11,[13][14][15][16]23]. The most reported barriers to the utilization of dental care during pregnancy were low awareness of the importance of oral healthcare, negative perceptions regarding the safety of dental treatment, and lack of perceived need for dental care [11,14,16,[23][24].…”
Section: Introductionmentioning
confidence: 99%